A Cocoa Diet Can Partially Attenuate the Alterations in Microbiota and Mucosal Immunity Induced by a Single Session of Intensive Exercise in Rats - Ruiz-Iglesias, Patricia; Massot-Cladera, Malén; Rodríguez-Lagunas, Maria J.; Franch, Àngels; Camps-Bossacoma, Mariona; Castell, Margarida; Pérez-Cano, Francisco J. (Frontiers in Nutrition, 2022)
Background Following intensive sports events, a higher rate of upper respiratory tract infections and the appearance of gastrointestinal symptomatology have been reported. We aimed to evaluate the effect of a cocoa-enriched diet on the cecal microbiota and mucosal immune system of rats submitted to high-intensity acute exercise, as well as to elucidate the involvement of cocoa fiber in such effects. Methods Wistar rats were fed either a standard diet, a diet containing 10% cocoa providing 5% fiber and a diet containing only 5% cocoa fiber. After 25 days, half of the rats of each diet performed an exhaustion running test. Sixteen hours later, samples were obtained to assess, among others, the cecal microbiota and short chain fatty acids (SCFAs) composition, mesenteric lymph nodes (MLNs) and Peyer’s patches (PPs) lymphocyte composition, and immunoglobulin (Ig) content in salivary glands. Results The intake of cocoa, partially due to its fiber content, improved the SCFA production, prevented some changes in PPs and in MLNs lymphocyte composition and also decreased the production of proinflammatory cytokines. Cocoa diet, contrary to cocoa fiber, did not prevent the lower salivary IgM induced by exercise. Conclusion A cocoa dietary intake can partially attenuate the alterations in microbiota and mucosal immunity induced by a single session of intensive exercise.